X-ray rapid charging stress luminescent material and preparation method thereof
By adding Dy3+ and Li+ to A2SiO4 material, X-ray fast charging stress luminescent materials are prepared, which solves the problems of limited types of existing materials and single pre-excitation sources, and realizes the rapid charging of the material and long-term stress luminescent effects, expanding its application potential in various application fields.
Patent Information
- Application Number
- CN202510065085.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing types of stress luminescent materials are limited, and the pre-excitation source is single, which limits its development in practical applications.
A2SiO4 (A=Ca, Sr or Ba) material is used as the matrix, and trivalent rare earth ion Dy3+ is added as the activator and Li+ as the charge compensation agent to prepare a stress luminescent material with fast charging of X-rays by high-temperature solid phase method.
It realizes fast charging of materials and long-term afterglow and stress luminescence, expanding its application potential in fields such as smart wearable devices and mechanically driven light generators.
Smart Images

Figure CN119875626A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel inorganic functional materials, and in particular relates to an X-ray fast-charged stress luminescent material and a preparation method thereof. Background Art
[0002] Mechanoluminescence refers to the luminescence phenomenon of materials under various mechanical stimuli (such as friction, compression, stretching, vibration, impact, ultrasound, etc.) in a broad sense, and the luminescence phenomenon caused by elastic deformation, plastic deformation and fracture in a narrow sense. According to the characteristics of the material, stress luminescence can be divided into self-recovery type and pre-excited trap-controlled type. Trap-controlled stress luminescence material is a new type of energy storage and electron capture material. In the fields of stress distribution visualization, bridge engineering structure diagnosis, signature and anti-counterfeiting encryption, stress luminescence materials have broad application prospects. In addition, stress luminescence materials are also endowed with the potential of new optoelectronic materials for the new era, and are expected to achieve advanced functions such as self-driving, flexibility, and multi-mode coupling. Similarly, stress luminescence materials have gradually become one of the new research hotspots in cutting-edge fields such as smart wearable devices, mechanically driven light generators, biomedical diagnosis and treatment, artificial intelligence and electronic skin. Its potential application areas can cover many industries such as medicine, agriculture, information, military, and aviation. The research on stress luminescent materials has attracted much attention from scholars in recent years. Due to its many advantages such as recyclability and stress distribution image visualization, it has attracted worldwide attention, resulting in rapid development of the research on stress luminescent materials.
[0003] Compared with other types of luminescent materials, the research time of stress luminescent materials is relatively short. In 1999, Chaonan Xu's research group at the National Institute of Advanced Industrial Science and Technology of Japan first reported ZnS:Mn 2+ (yellow) and SrAl2O4:Eu 2+ (Green) Since the emergence of these two extremely bright stress luminescent materials, the types of stress luminescent materials that have been successfully synthesized so far are still very limited. The lack of types is one of the important factors that affect the development of stress luminescent materials in practical applications. Studies have shown that the fastest way to develop stress luminescent materials is to screen out materials with non-centrosymmetric crystal structures from existing long-lasting luminescent materials. Representative materials include: CaZr(PO4)2:Eu 2+ 、Sr3Al2O5Cl2:Eu 2+ ,Tm 3+ 、BaSi2O2N2:Eu 2+ 、Ca2Al2SiO7:Eu 2+ ,Dy 3+In addition, most of the current stress luminescent materials have a relatively single pre-excitation source, and expanding the pre-excitation source is also one of the methods to improve the performance of stress luminescent materials. Therefore, developing a chemically stable, non-toxic, simple preparation method, and using high-energy rays (such as X-rays) as a pre-excitation source in this field will also have a great driving force for the research and application of stress luminescent materials. Summary of the invention
[0004] The purpose of the present invention is to provide an X-ray fast charging stress luminescent material and its preparation method. 3+ As activator, Li + As a charge compensator, the X-ray fast-charged force-induced fluorescent powder A was prepared 2-x-y SiO4:xDy 3+ ,yLi + (A = Ca, Sr or Ba, 0 < x ≤ 0.08, 0 < y ≤ 0.07), where Dy doped in silicate 3+ With Li + Form traps in the matrix to capture carriers; by changing Dy 3+ With Li + The concentration of carriers inside the trap can be adjusted by adjusting the concentration of the trap, so that it has strong afterglow and mechanoluminescence intensity. The material is simple to prepare, has stable chemical properties, short excitation time, strong afterglow and afterglow duration, strong stress luminescence phenomenon, and it exhibits ultra-long delayed stress luminescence phenomenon. The stress luminescence performance of the fluorescent powder provided by the present invention lays a foundation for its practical application in many fields such as intelligent wearable devices, mechanically driven light generators, biomedical diagnosis and treatment, artificial intelligence and electronic skin, stress sensing, bridge damage detection, anti-counterfeiting encryption, etc.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide an X-ray fast charging induced fluorescent powder, the chemical formula of the X-ray fast charging induced fluorescent powder is: 2-x-y SiO4:xDy 3+ ,yLi + ; Wherein, A is Ca, Sr or Ba, 0<x≤0.08, 0<y≤0.07.
[0007] The second technical solution of the present invention is to provide a method for preparing the above-mentioned X-ray fast charging induced fluorescent powder by a high temperature solid phase method.
[0008] Preferably, the specific steps of the high-temperature solid phase method preparation include: weighing the carbonate of element A and Li, and the oxides of Si and Dy in proportion, adding a dispersion, grinding and mixing, and pre-firing under aerobic conditions, grinding the pre-firing product and continuing to calcine under aerobic conditions to obtain the X-ray fast charging capable fluorescent powder.
[0009] Preferably, the dispersion liquid is anhydrous ethanol.
[0010] Preferably, the pre-firing temperature is 800-900° C. and the time is 2-4 hours.
[0011] Preferably, the calcination temperature is 1200-1300° C. and the calcination time is 4-6 hours.
[0012] More preferably, the heating rates of the pre-sintering and the calcining are both 5-10° C. / min.
[0013] The third technical solution of the present invention is to provide an X-ray fast charging stress luminescent material, which is composed of the above-mentioned X-ray fast charging stress luminescent powder dispersed in a cured epoxy resin.
[0014] A fourth technical solution of the present invention is to provide a method for preparing the above-mentioned X-ray fast-charged stress luminescent material, comprising the following steps:
[0015] The X-ray fast charging stress luminescent powder is mixed with epoxy resin and curing agent, and the X-ray fast charging stress luminescent material is obtained after curing.
[0016] The fifth technical solution of the present invention is to provide an application of the above-mentioned X-ray fast charging induced fluorescent powder in the preparation of stress luminescent devices.
[0017] Technical solution six of the present invention: provides an application of the above-mentioned X-ray fast-charged stress luminescent material in the preparation of a stress luminescent device.
[0018] The beneficial technical effects of the present invention are as follows:
[0019] The X-ray fast charging energy-induced fluorescent powder provided by the present invention is prepared by a traditional high-temperature solid phase method, and has a simple preparation process, easy control of conditions, low equipment requirements, and low cost. No toxic gas is generated during the preparation process, and there is no pollution to the environment.
[0020] The X-ray fast-charged stress luminescent material prepared by the present invention can emit an afterglow visible to the naked eye in a dark environment after a short period of X-ray pre-excitation and the excitation source is turned off, and the afterglow lasts for more than 8 hours; under the pressure stimulation of an external load, a stress luminescence phenomenon visible to the naked eye can be observed, and after 386 hours, the stress luminescence signal can still be detected under the action of an external load.
[0021] The X-ray fast charging energy-induced fluorescent powder provided by the present invention can be mixed with organic polymers such as epoxy resin and curing agent to prepare stress luminescent devices in various forms. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD patterns of the differently doped strontium silicate powders and α-strontium silicate and β-strontium silicate prepared in Examples 1 to 11, wherein (a) is the XRD pattern of the differently doped strontium silicate powders and α-strontium silicate and β-strontium silicate prepared in Examples 1 to 7, and (b) is the XRD pattern of the differently doped strontium silicate powders and α-strontium silicate and β-strontium silicate prepared in Examples 8 to 11.
[0023] Figure 2 The afterglow emission spectra of the differently doped strontium silicate powders prepared in Examples 1 to 11 measured after 10 seconds of X-ray excitation, wherein (a) is the afterglow emission spectrum of the differently doped strontium silicate powders prepared in Examples 1 to 7, and (b) is the afterglow emission spectrum of the differently doped strontium silicate powders prepared in Examples 6 and 8 to 11.
[0024] Figure 3 The afterglow decay curve of the differently doped strontium silicate powder prepared in Example 9 was measured at 481 nm after being excited by X-rays for 10 seconds.
[0025] Figure 4 The stress luminescence intensity at 481 nm of the doped strontium silicate stress luminescent material prepared in Examples 12 to 18 after X-ray excitation for 10 s and 1 min interval and 5 cycles of compression under a load of 1000 N, wherein (a) is the stress curve during the five cycles of compression, (b) to (h) are the stress luminescence intensities of Examples 12 to 18, and (i) is the stress luminescence intensity of different Dy 3+ Stress luminescence intensity as a function of doping concentration.
[0026] Figure 5 The stress luminescence intensity at 481 nm of the doped strontium silicate stress luminescent materials prepared in Examples 17 and 19 to 22 after being excited by X-rays for 10 s and compressed for 5 times under a load of 1000 N with an interval of 1 min, wherein (a) to (e) are the stress luminescence intensities of Examples 17 and 19 to 22, respectively, and (f) is the stress luminescence intensity of different Li + Stress luminescence intensity as a function of doping concentration.
[0027] Figure 6 The stress luminescence curve at 481 nm was obtained by applying a cyclic compressive load to the doped strontium silicate stress luminescent material prepared in Example 20 after being excited by X-rays for 5 minutes and delayed for 386 hours in the dark. DETAILED DESCRIPTION
[0028] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0029] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the invention.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] Unless otherwise specified, the "room temperature" in the embodiments of the present invention refers to a temperature of 20±10°C.
[0033] Examples 1 to 11
[0034] Preparation of doped strontium silicate powder:
[0035] According to the molar ratio of metal elements and silicon in Table 1, analytically pure SrCO3, SiO2, Dy2O3 and Li2CO3 (Li2CO3 is not added in Examples 1 to 7) are weighed, 5 mL of anhydrous ethanol is added, and the mixture is transferred to a crucible and placed in a muffle furnace after being fully ground. The mixture is heated to 800°C at 5°C / min in an air environment, and naturally cooled to room temperature in the furnace after pre-burning for 2 hours; the powder in the crucible is taken out, fully ground in an agate mortar, transferred to a crucible, placed in a muffle furnace, and heated to 1300°C at 5°C / min in an air environment. After calcination for 6 hours, the mixture is naturally cooled to room temperature in the furnace. The powder in the crucible is taken out, and fully ground in an agate mortar to obtain doped strontium silicate powder.
[0036] Table 1
[0037]
[0038]
[0039] The XRD spectra of the differently doped strontium silicate powders prepared in Examples 1 to 11, α-strontium silicate and β-strontium silicate are shown in Figure 1 , wherein (a) is the XRD spectrum of the differently doped strontium silicate powders and α-strontium silicate and β-strontium silicate prepared in Examples 1 to 7, and (b) is the XRD spectrum of the differently doped strontium silicate powders and α-strontium silicate and β-strontium silicate prepared in Examples 6 and 8 to 11. Figure 1 It shows that the doped strontium silicate powder prepared by the present invention is pure phase, and the doped ions do not disturb the crystal structure.
[0040] The afterglow emission spectra of the differently doped strontium silicate powders prepared in Examples 1 to 11 measured after 10 seconds of X-ray excitation are shown in FIG. Figure 2 , wherein (a) is the afterglow emission spectrum of the differently doped strontium silicate powders prepared in Examples 1 to 7, and (b) is the afterglow emission spectrum of the differently doped strontium silicate powders prepared in Examples 6 and 8 to 11. Figure 2 The emission peaks of the afterglow spectrum are approximately at 481, 574, 663 and 752 nm, which are displayed in white and are Dy 3+ characteristic transition and has strong afterglow emission intensity.
[0041] Figure 1 and Figure 2 0Li + This is the sample of Example 6.
[0042] The afterglow decay curve of the differently doped strontium silicate powders prepared in Example 9 at 481 nm was measured after 10 seconds of X-ray excitation. Figure 3 . Figure 3 It shows that the Sr prepared in Example 8 1.9 SiO4:0.07Dy 3+ ,0.03Li + After 10 seconds of X-ray excitation, the afterglow decay time can last for more than 8 hours.
[0043] Examples 12 to 22
[0044] Preparation of doped strontium silicate stress luminescent materials:
[0045] A mixed solution of epoxy resin and curing agent was prepared with a volume ratio of epoxy resin to curing agent of 2:1, 0.5 mL of the mixed solution was taken, and 0.5 g of the doped strontium silicate powder prepared in Examples 1 to 11 was added to the mold (diameter 25 mm, depth 15 mm), and the mixture was allowed to stand for 4 hours after being stirred evenly. 5.5 mL of the mixed solution was added to the mold again and allowed to stand for 24 hours to obtain a doped strontium silicate stress luminescent material.
[0046] The doped strontium silicate stress luminescent materials of Examples 12 to 22 correspond to the doped strontium silicate powders of Examples 1 to 11, respectively.
[0047] The stress luminescence intensity at 481 nm of the doped strontium silicate stress luminescent materials prepared in Examples 12 to 18 was 10 s after X-ray excitation and 1 min interval, and then compressed 5 times under a load of 1000 N. Figure 4 , where (a) is the stress curve during five cycles of compression, (b) to (h) are the stress luminescence intensities of Examples 12 to 18, and (i) is the stress luminescence intensity of different Dy 3+ Stress luminescence intensity as a function of doping concentration.
[0048] The stress luminescence intensity at 481 nm of the doped strontium silicate stress luminescent materials prepared in Examples 17, 19 to 22 was 10s after X-ray excitation and 1min interval, and then compressed 5 times under a load of 1000N. Figure 5 , where (a) to (e) are the stress luminescence intensities of Examples 17, 19 to 22, respectively, and (f) is the stress luminescence intensities of different Li + Stress luminescence intensity as a function of doping concentration.
[0049] Figure 5 0Li + This is the sample of Example 17.
[0050] Figure 4 and Figure 5 It shows that in a weak light environment, after the excitation source is removed, the doped strontium silicate stress luminescent materials prepared in Examples 19 to 22 still have good stress luminescent properties.
[0051] The stress luminescence curve of the doped strontium silicate stress luminescent material prepared in Example 20 at 481 nm was measured after 5 min of X-ray excitation and 386 h of delay in the dark and then applying a cyclic compression load. Figure 6 . Figure 6 It is shown that after a short period of X-ray charging, under the action of external mechanical stimulation, the doped strontium silicate stress luminescent material prepared in Example 20 exhibits an ultra-long delayed stress luminescence phenomenon.
[0052] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An X-ray fast charging fluorescent powder, characterized in that: The chemical formula of the X-ray fast charging induced fluorescent powder is: 2-x-y SiO4:xDy 3+ ,yLi + ; Wherein, A is Ca, Sr or Ba, 0<x≤0.08, 0<y≤0.
07.
2. A method for preparing the X-ray fast charging induced fluorescent powder according to claim 1, characterized in that: Prepared by high temperature solid phase method.
3. The method for preparing the X-ray fast charging induced fluorescent powder according to claim 2, characterized in that: The specific steps of the high-temperature solid phase method preparation include: weighing the carbonate of element A and Li, and the oxides of Si and Dy in proportion, adding a dispersion, grinding and mixing, and then pre-sintering under aerobic conditions, and then grinding the pre-sintered product and continuing to calcine under aerobic conditions to obtain the X-ray fast charging ability-induced fluorescent powder.
4. The method for preparing the X-ray fast charging induced fluorescent powder according to claim 3, characterized in that: The dispersion liquid is anhydrous ethanol.
5. The method for preparing the X-ray fast charging induced fluorescent powder according to claim 3, characterized in that: The pre-sintering temperature is 800-900° C., and the time is 2-4 hours; and / or, the calcining temperature is 1200-1300° C., and the time is 4-6 hours.
6. The method for preparing the X-ray fast charging induced fluorescent powder according to claim 5, characterized in that: The heating rates of the pre-sintering and the calcining are both 5-10°C / min.
7. An X-ray fast-charged stress luminescent material, characterized in that: The X-ray fast charging energy-induced fluorescent powder according to claim 1 is dispersed in a cured epoxy resin.
8. A method for preparing the X-ray fast-charged stress luminescent material according to claim 7, characterized in that: The following steps are involved: The X-ray fast charging stress luminescent powder is mixed with epoxy resin and curing agent, and the X-ray fast charging stress luminescent material is obtained after curing.
9. Use of the X-ray fast charging induced fluorescent powder according to claim 1 in the preparation of stress luminescent devices.
10. Use of the X-ray fast-charged stress luminescent material according to claim 7 in preparing stress luminescent devices.
Citation Information
Patent Citations
Yellow silicate long-lasting luminescent material and preparation method thereof
CN105778898A
Stress luminescent material with orange-yellow afterglow and preparation thereof
CN113999672A
X-ray excited borate long-afterglow luminescent material and preparation method thereof
CN118703203A